Gender, nutrition-sensitive agricultural interventions, and resilience: Evidence from rural Bangladesh - Hoddinott, John F.; Ahmed, Akhter; Bakhtiar, M. Mehrab; Quisumbing, Agnes R. (International Food Policy Research Institute, 2025)
We assess whether a gender- and nutrition-sensitive agricultural interventions, fielded in rural Bangladesh, aimed at improving food production diversity enhanced resilience and whether impacts persisted post-intervention. Four years post-program, treatment arms that included both agriculture and nutrition training reduced the likelihood that households undertook more severe forms of coping strategies during the Covid-19 pandemic. There were persistent improvements in household consumption and diet quality; impacts were largest for poor but not the poorest households in our sample. Underlying these results were the long-term beneficial impacts on women’s agricultural knowledge, agency, and increased engagement in agricultural activities.